2015
DOI: 10.1002/wics.1363
|View full text |Cite
|
Sign up to set email alerts
|

Robust statistics: a selective overview and new directions

Abstract: Classical statistics relies largely on parametric models. Typically, assumptions are made on the structural and the stochastic parts of the model and optimal procedures are derived under these assumptions. Standard examples are least squares estimators in linear models and their extensions, maximum-likelihood estimators and the corresponding likelihood-based tests, and generalized methods of moments (GMM) techniques in econometrics. Robust statistics deals with deviations from the stochastic assumptions and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Understanding that error distributions are often almost-Cauchy should encourage use of t-based [96], median [97], and other robust statistical methods [98], and supports choosing Student-t [99] or Cauchy [100] priors in Bayesian analysis. Outlier-tolerant methods are already common in modern meta-analysis, so there should be little effect on accepted values of quantities with multiple published measurements, but this better understanding of the uncertainty may help improve methods and encourage consistency.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding that error distributions are often almost-Cauchy should encourage use of t-based [96], median [97], and other robust statistical methods [98], and supports choosing Student-t [99] or Cauchy [100] priors in Bayesian analysis. Outlier-tolerant methods are already common in modern meta-analysis, so there should be little effect on accepted values of quantities with multiple published measurements, but this better understanding of the uncertainty may help improve methods and encourage consistency.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the effect of each individual observation on the result of a statistical analysis should be an essential ingredient of any applied statistical work. This goal is typically out of reach for classical diagnostic techniques, either from a model-based or a geometric perspective, since they can be grossly distorted in the presence of contamination by outliers, or under systematic deviation from the postulated data generating mechanism (Maronna et al, 2006;Huber and Ronchetti, 2009;Avella-Medina and Ronchetti, 2015;Farcomeni and Greco, 2015). As a consequence, frequent examples can be found that use numerical and graphical inspection of robust residuals in regression and of robust Mahalanobis distances with multivariate data; see, e.g., Hubert et al (2008) for an overview.…”
Section: Introductionmentioning
confidence: 99%
“… 5. More information on the aims of robust statistics is given in an essay by Morgenthaler (2007) and in a more technical overview by Avella-Medina and Ronchetti (2015). The interested reader can find detailed technical descriptions of commonly used robust statistical methods in Maronna et al (2006). …”
mentioning
confidence: 99%